Evaluation of cumulative dose for cone‐beam computed tomography (CBCT) scans within phantoms made from different compositions using Monte Carlo simulations. (8th November 2015) - Abuhaimed, Abdullah; Martin, Colin J.; Sankaralingam, Marimuthu; Oomen, Kurian; Gentle, David J.
Abstract : Measurement of cumulative dose f ( 0, 150 ) with a small ionization chamber within standard polymethyl methacrylate (PMMA) CT head and body phantoms, 150 mm in length, is a possible practical method for cone‐beam computed tomography (CBCT) dosimetry. This differs from evaluating cumulative dose under scatter equilibrium conditions within an infinitely long phantom f ( 0, ∞ ), which is proposed by AAPM TG‐111 for CBCT dosimetry. The aim of this study was to investigate the feasibility of using f ( 0, 150 ) to estimate values for f ( 0, ∞ ) in long head and body phantoms made of PMMA, polyethylene (PE), and water, using beam qualities for tube potentials of 80 − 140   k V . The study also investigated the possibility of using 150 mm PE phantoms for assessment of f ( 0, ∞ ) within long PE phantoms, the ICRU/AAPM phantom. The influence of scan parameters, composition, and length of the phantoms was investigated. The capability of f ( 0, 150 ) to assess f ( 0, ∞ ) has been defined as the efficiency and assessed in terms of the ratios ϵ ( f ( 0, 150 ) / f ( 0, ∞ ) ) . The efficiencies were calculated using Monte Carlo simulations for an On‐Board Imager (OBI) system mounted on a TrueBeam linear accelerator. Head and body scanning protocols with beams of width 40 − 500   mm were used. Efficiencies ϵ ( PMMA / PMMA ) and ϵ ( PE / PE ) as a function of beam width exhibited three separate regions. For beam widths < 150   mm, ϵ ( PMMA / PMMA ) and ϵ ( PE / PE ) values were greater than 90% for the head and body phantoms. The efficiency values then fell rapidly with increasing beam width before levelling off at 74% for ϵ ( PMMA / PMMA ) and 69% for ϵ ( PE / PE ) for a 500 mm beam width. The quantities ϵ ( PMMA / PE ) and ϵ ( PMMA / Water ) varied with beam width in a different manner. Values at the centers of the phantoms for narrow beams were lower and increased to a steady state for ∼ 100 − 150   mm wide beams, before declining with increasing the beam width, whereas values at the peripheries decreased steadily with beam width. Results for ϵ ( PMMA / PMMA ) were virtually independent of tube potential, but there was more variation for ϵ ( PMMA / PE ) and ϵ ( PMMA / Water ) . f ( 0, 150 ) underestimated f ( 0, ∞ ) for beam widths used for CBCT scans, thus it is necessary to use long phantoms, or apply conversion factors ( C f s ) to measurements with standard PMMA CT phantoms. The efficiency values have been used to derive ( C f s ) to allow evaluation of f ( 0, ∞ ) from measurements of f ( 0, 150 ) . The ( C f s ) only showed a weak dependence on scan parameters and scanner type, and so may be suitable for general application. PACS number: 87.55.K‐, 87.57.Q‐, 87.57.uq.